Chromosomal evolution and biogeography of collared lemmings ( Dicrostonyx ) in the eastern and High Arctic of Canada - Borowik, Oksana A.; Engstrom, Mark D. (Canadian Journal of Zoology, 1993)
Chromosomal variation was examined in 10 populations of Dicrostonyx in the eastern and High Arctic of Canada to determine the extent and nature of chromosomal variation and to examine chromosomal differentiation within and among species and subspecies. Chromosomal data are presented for two species of collared lemmings, D. hudsonius and D. groenlandicus, including D. g. groenlandicus, D. g. clarus, and D. g. lentus. Standard, G-banded, and C-banded karyotypes revealed variation among populations of D. groenlandicus due to Robertsonian fusions and the addition of B chromosomes. G-banding revealed complete homologous banding patterns of autosomal arms between D. groenlandicus and D. hudsonius; however, sex chromosome constitution differed between the two species. Dicrostonyx groenlandicus possesses a neo-XY, formed by a Robertsonian fusion of the sex chromosomes and a pair of autosomes. The neo-XY does not occur in D. hudsonius, and this absence appears to be the primitive state for the genus.